Хутагт, хувилгаадаас хэд нь үлдээд байгаа бол : Ноён хутагт Данзанрабжайн Хонгор хийд (Journal of International Studies, 2000)
English title: Currently, how many khutugtu (saints) are alive? The temple "Khongor" of Danzanravjaa khutugtu